Identification of Hydrocarbon Reservoir Distribution Using Seismic Attributes: RMS Amplitude and Sweetness in the Bani Field, South Sumatra Basin - Tamba, Shallsa Bella. W; Adhi, M. Aryono; Nurcahya, Budi Eka (Universitas Negeri Semarang, 2023)
The Bani Field is in the South Sumatra basin, which is considered to have potential hydrocarbon reserves. The seismic reflection method is one method that can be used to describe geological conditions. In addition, this method is also able to provide analyses related to the presence of hydrocarbon reserves in the form of oil and gas, where one of the analyses that can be used is seismic attributes. In this study, the seismic attributes used are the RMS Amplitude and the Sweetness attribute, both of which play a role in identifying subsurface structures and determining hydrocarbon indicators. This study was conducted to analyze the results of the application of the RMS amplitude attribute and the sweetness attribute in determining the distribution of hydrocarbon reservoirs and analyzing the results of the application of the variance attribute in detecting the fault structure of the Bani Field. From the results of the analysis using the RMS amplitude attribute, the Batu Raja Formation layer describes a good response with a yellow to reddish brown color scale with a value scale between 220,000 to 320,000 ms, while the Talang Akar Formation layer describes a good response with a value scale of 160,000 to 240,000 ms. The analysis using the sweetness attribute confirmed the interpretation of the RMS amplitude attribute, indicating the presence of hydrocarbons, as depicted by the sweet spot region. Meanwhile, the geometrical attribute analysis used, namely structural smoothing and variance attributes, helped map structures and identify faults.